Pulmonary artery denervation by noninvasive stereotactic radiotherapy: a pilot study in swine models of pulmonary hypertension - Xingxing Cai; Zhixing Wei; Yichen Shen; Li Qian; Jing Cai; Yuli Yang; Runmin Chi; Wei Wang; Shunxuan Yu; Keke Li; Yudong Fei; Cheng Li; et al. (Nature Communications)
Abstract Catheter-based pulmonary artery denervation (PADN) has achieved promising outcomes to treat pulmonary hypertension (PH). We herein present stereotactic body radiotherapy (SBRT) as a novel noninvasive approach for PADN. A single fraction of 15 Gy, 20 Gy or 25 Gy was delivered for PADN in a thromboxane A2 (TxA2) - induced acute PH swine model. We demonstrated that PADN by 20-Gy SBRT reduced mean pulmonary artery (PA) pressure during the TxA2 challenge. All SBRT dosages led to a deeper denervation area compared with radiofrequency ablation (RFA) and reduced sympathetic neural norepinephrine synthesis in the ablation zone. Probable radiation related side effects were mostly found in animals treated with 25-Gy. In subsequent monocrotaline-induced chronic PH animals, PADN by 20-Gy SBRT resulted in more significant improvement in pulmonary hemodynamics and PA remodeling in comparison to RFA. In summary, our findings suggest that appropriate SBRT scheme could balance the efficacy and safety for PADN, potentiating to be a novel strategy to treat PH.